2018
DOI: 10.1111/epi.14549
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the screening, diagnosis, and management of ADHD in children with epilepsy. Consensus paper of the Task Force on Comorbidities of the ILAE Pediatric Commission

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common and challenging comorbidity affecting many children with epilepsy. A working group under the International League Against Epilepsy (ILAE) Pediatric Commission identified key questions on the identification and management of ADHD in children with epilepsy. Systematic reviews of the evidence to support approaches to these questions were collated and graded using criteria from the American Academy of Neurology Practice Parameter. Preferred Reporting Item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 84 publications
2
94
0
8
Order By: Relevance
“…Considering the high prevalence of functional disabilities (e.g., learning difficulties) among PWE, routine screening of all PWE for early detection and appropriate management of any cognitive dysfunction and functional disability would be a reasonable approach. 15,16 However, these findings should be seen and interpreted in the context of sociocultural backgrounds. For example, in 2019, Iran's unemployment rate was estimated to be 12% of the total labor force 17 ; this is much lower than the 53% rate in PWE in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…Considering the high prevalence of functional disabilities (e.g., learning difficulties) among PWE, routine screening of all PWE for early detection and appropriate management of any cognitive dysfunction and functional disability would be a reasonable approach. 15,16 However, these findings should be seen and interpreted in the context of sociocultural backgrounds. For example, in 2019, Iran's unemployment rate was estimated to be 12% of the total labor force 17 ; this is much lower than the 53% rate in PWE in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…The Task Force on Comorbidities of the International League Against Epilepsy Pediatric Commission recommends methylphenidate as the first-choice treatment because there is a 65% to 83% improvement in ADHD symptoms without significantly increasing the frequency or severity of seizures. 207 Atomoxetine has also shown efficacy in treating ADHD in this population, but there is limited evidence regarding safety. 207…”
Section: Epilepsymentioning
confidence: 99%
“…207 Atomoxetine has also shown efficacy in treating ADHD in this population, but there is limited evidence regarding safety. 207…”
Section: Epilepsymentioning
confidence: 99%
“…More recently, another open-label study that enrolled 30 epilepsy patients and ADHD showed that only one out of these 30 patients withdrew methylphenidate after seizure worsening [10]. Auvin A et al, in 2018 [11], reported in a systematic review the screening tools, diagnosis, and management of ADHD in children with epilepsy and underlined the risks and difficulties of pharmacological treatments of these patients: as the underdiagnosis of ADHD, possible attention and behavioral worsening due to AEDs and, on the other hand, the false myth that stimulants may lower the seizure threshold.…”
Section: Therapeutic Implications For Drugs For Adhdmentioning
confidence: 99%
“…Among the first generation AEDs, the most documented association of AEDs with behavioral disturbances and hyperactivity is about phenobarbital [PB] that can induce symptoms of ADHD, followed by valproic acid [VPA] and topiramate [TPM] [6,13]. A double-blind, randomized controlled trial that evaluated short term effects on attention skills of ethosuximide [ETS], VPA and lamotrigine [LTG], showed attention deficit in 49% of patients treated with VPA, 32% of those receiving ETS, and 24% of those receiving LTG [13] [11,14] The behavioral effects (in terms of hyperactivity disturbances, irritability, and disinhibition) of the main AEDs are reported in Table 1.…”
Section: Therapeutic Implications For Aedsmentioning
confidence: 99%